Possible correlation between nighttime lighting data and building height - Kazawa, Go; Seki, Daikichi; Keola, Souknilanh; Iwasaki, Fusanori; Yamashiki, Yosuke Alexandre (Frontiers in Sustainability, 2022)
This study examined whether nighttime light can be a proxy for building height. It is important for estimating an urban environment and urban design and understanding industrial clusters. However, it is necessary to purchase height data for a wide range of buildings, and it is difficult to obtain data in a time series. In this study, we examined whether it is possible to estimate the height of buildings using nighttime light data. This research focuses on the fact that as the number of windows increases, the amount of light leaking from the windows during the night increases for the entire building. This increases the amount of light emitted by the building. We conducted the first Japanese correlation analysis using a three-dimensional dataset with a resolution of 1 meter that was released by Hyogo Prefecture on 10 January 2020. We also used nighttime light data from the Suomi NPP satellite, which has been in operation since 2011 and is jointly managed by National Oceanic and Atmospheric Administration and NASA. The percentage of land occupied by buildings within a 450-meter square of a nighttime light resolution was varied to obtain a higher correlation between buildings and nighttime light. The correlation between the average height of buildings and the luminous intensity of nighttime light within that pixel was calculated. The coefficient of determination was 0.425, which was the best value when the percentage of land occupied by buildings in a pixel was between 70 and 80%. This study found a high correlation between night light and building height. We believe that if a building has a certain size, the night light can be used as a proxy. The results of our research will contribute to understanding the changes and characteristics of urban development and population distribution as urbanization progresses in various regions. Rapid public transportation services, education, and environmental improvement will contribute to urban development and changes in population distribution, which will greatly relieve urban poverty and improve urban security and the environment.